2009
DOI: 10.1534/genetics.109.101808
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Unanticipated Alleles of lethal giant larvae in Drosophila Second Chromosome Stocks

Abstract: Forty years ago, a high frequency of lethal giant larvae (lgl) alleles in wild populations of Drosophila melanogaster was reported. This locus has been intensively studied for its roles in epithelial polarity, asymmetric neural divisions, and restriction of tissue proliferation. Here, we identify a high frequency of lgl alleles in the Bloomington second chromosome deficiency kit and the University of California at Los Angeles Bruinfly FRT40A-lethal P collection. These unrecognized aberrations confound the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 28 publications
(38 reference statements)
0
30
0
Order By: Relevance
“…Among these are the Polycomb group (PcG) genes, which in some studies have been proposed to act as dominant suppressors of TPE [Su(TPE)] and whose encoded proteins have been found to be located at the telomeric regions of polytene chromosomes (6). These findings indicate that TPE is a distinctive class of chromatin silencing which shares mechanistic features with both pericentromeric heterochromatin and PcG-mediated silencing of developmental regulators.The extent to which PcG proteins and other reported Su(TPE) bind at TAS repeats and modify TPE, though, has become less clear since the finding of a high incidence of TPE-suppressing terminal deletions on chromosome 2L in public Drosophila mutant stocks (38,46). This leads to a high rate of false-positive identifications of Su(TPE), in which the modifying activity is attributable to the 2L deletion, which eliminates the TAS repeats at that location and suppresses TPE in trans, rather than to the mutant gene being tested (38).…”
mentioning
confidence: 99%
“…Among these are the Polycomb group (PcG) genes, which in some studies have been proposed to act as dominant suppressors of TPE [Su(TPE)] and whose encoded proteins have been found to be located at the telomeric regions of polytene chromosomes (6). These findings indicate that TPE is a distinctive class of chromatin silencing which shares mechanistic features with both pericentromeric heterochromatin and PcG-mediated silencing of developmental regulators.The extent to which PcG proteins and other reported Su(TPE) bind at TAS repeats and modify TPE, though, has become less clear since the finding of a high incidence of TPE-suppressing terminal deletions on chromosome 2L in public Drosophila mutant stocks (38,46). This leads to a high rate of false-positive identifications of Su(TPE), in which the modifying activity is attributable to the 2L deletion, which eliminates the TAS repeats at that location and suppresses TPE in trans, rather than to the mutant gene being tested (38).…”
mentioning
confidence: 99%
“…3). Using the muscle-specific 24b-Gal4 driver (Brand and Perrimon, 1993) to express UAS-lgl (Roegiers et al, 2009) in the postsynaptic muscle cells of otherwise lgl null mutants, we observed improved larval motility and growth rates similar to heterozygous siblings, even when reared in competition (data not shown). At the NMJ, however, postsynaptic LGL expression provided no improvement of synaptic morphology (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…RNAi experiments were performed using a w; lglRNAi/lgl-RNAi line (w; P{GD4047}v51247; Dickson et al, 2007) crossed to either the muscle-specific Gal4 driver 24b (w; 24b-Gal4/24b-Gal4; Brand and Perrimon, 1993;Nitabach et al, 2006;Rohrbough and Broadie, 2010) or the neuron-specific Gal4-driver elav (w; elav-Gal4/y; Luo et al, 1994;Rohrbough and Broadie, 2010). Rescue experiments were done on lines generated from a cross between UAS-lgl; lgl u334 /CyOKrGFP males (Roegiers et al, 2009), and virgin females from (1) lgl 1 /croKrGFP; uh1-Gal4 for ubiquitous expression (w; +; uh1-Gal4; Wodarz et al, 1995), (2) lgl 1 /CyOKrGFP; 24b-Gal4 for muscle expression or (3) elav-Gal4; lgl 1 /CyOKrGFP for neuronal expression. To control for background effects of Gal4 drivers, a single copy of each Gal4 driver alone was crossed into the lgl control background (uh1-Gal4/+, 24b-Gal4/+ and elav-Gal4/+).…”
Section: Genetic Stocksmentioning
confidence: 99%
“…These images resemble scanning electron micrographs of fly cuticle, but can be acquired from live animals, and allow us to simultaneously visualize cuticular morphology and expression of GFP fluorescence 6,7,12 .…”
Section: Discussionmentioning
confidence: 99%